Personnel Management within the Conditions of New Social-Economic Reality - Marchenko, Оksana A.; Starko , Iryna E.; Motuzenko, Oksana V.; Vdovichena, Olga H.; Makarenko, Maksym V.; Мотузенко, Оксана Володимирівна (Ascociacion Internacional de Economia Aplicada, 2021)
The purpose of the academic paper is to study the new personnel management system within the conditions of external shocks (pandemic). The methodology is based on quantitative and qualitative methodology using in-depth interview methods with the HR Project Director for Cement JSC "Podilsky Cement" and Director on Projects in the sphere of Cement Personnel, CRH Ukraine, content analysis of the company's websites, statistical analysis of financial statements in order to determine the effectiveness of personnel management programs. The results prove that within the conditions of new social-economic reality through external shocks (pandemic) a new system of personnel management is formed, which through technology transforms the threats of management (hiring, employment) into opportunities for development and training, mentoring, internships by reducing staff turnover. Thus, the positive effect emerges of replacing the negative consequences of the virus spreading with the potential for human resources' development through effective virtual communication. External shocks cause a change in the social variables of the organization through the transformation of values, motivation, efficiency of employees. Within the pandemic conditions, the value of the collective atmosphere for employees increases, which will have a medium-term effect in the form of increased financial performance of organizations. The practical significance of the results lies in the possibility of using the results in human resource management, namely the integration of technology into personnel management in order to establish virtual communications. © 2020 Estudios de Economia Aplicada. All rights reserved.
Keywords: Human resource management; Management system; Pandemic conditions; The effectiveness of programs